2020
DOI: 10.1111/are.14974
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of Lactobacillus fermentum URLP18 on growth, innate immunity and survival against Aeromonas hydrophila ATCC 7966 challenge in freshwater fish Cyprinus carpio (common carp)

Abstract: Probiotics utilization in aquaculture is getting great potential due to their functional attributes. The present study elucidates the effects of dietary supplementation of probiotic Lactobacillus fermentum URLP18 on growth performance, antioxidants, haematological indices, immune regulatory gene expression and disease resistance in juveniles of Cyprinus carpio. Fish were fed for 60 days with basal diet (BD) and diet supplemented with L. fermentum URLP18 at 2 × 108 CFU/g (DI) and 2 × 106 CFU/g (DII). Dietary su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 76 publications
3
10
0
Order By: Relevance
“…Fish fed supplemented diets also had lower FCR levels. These results are in agreement with previous studies on beneficial effects of dietary pre-, pro-and synbiotics on growth performance parameters, including, diets supplemented with probiotics for juvenile roach (Rutilus rutilus) [58], common carp [59], Nile tilapia (Oreochromis niloticus) [60], Asian sea bass, (Lates calcarifer) [61], white shrimp [62] synbiotic in Texas cichlid (Herichthys cyanoguttatus) [31], and prebiotics in rainbow trout (Oncorhynchus mykiss) [22]. Dietary pre-and probiotics and their combination can stimulate fish appetite and intestinal microflora [63].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Fish fed supplemented diets also had lower FCR levels. These results are in agreement with previous studies on beneficial effects of dietary pre-, pro-and synbiotics on growth performance parameters, including, diets supplemented with probiotics for juvenile roach (Rutilus rutilus) [58], common carp [59], Nile tilapia (Oreochromis niloticus) [60], Asian sea bass, (Lates calcarifer) [61], white shrimp [62] synbiotic in Texas cichlid (Herichthys cyanoguttatus) [31], and prebiotics in rainbow trout (Oncorhynchus mykiss) [22]. Dietary pre-and probiotics and their combination can stimulate fish appetite and intestinal microflora [63].…”
Section: Discussionsupporting
confidence: 93%
“…Increased nutritional efficiency may be associated with improving digestive enzyme activity and degradation of indigestible nutrients, making them available for adsorption [59]. Probiotic supplements not only colonize intestinal epithelial cells but also adhere to the mucosa [9].…”
Section: Discussionmentioning
confidence: 99%
“…Ahmadifar et al (2019) investigated the probiotic role of L. fermentum and obtained better growth and immune responses in the supplemented fish. Similar results were observed in the study of Krishnaveni et al (2021), where a diet containing L. Fermentum improved growth, immunity and resistance against Aeromonas hydrophila in common carp ( Cyprinus carpio ). Besides probiotics, many studies have shown that medicinal plants can also improve fish immunity and resistance to diseases (Awad & Awaad, 2017; Galina et al, 2009; Van Hai, 2015).…”
Section: Introductionsupporting
confidence: 90%
“…It has been reported that A . hydrophila infection in common carp Cyprinus carpio can enhance the GOT and GPT activity in the serum (Krishnaveni et al, 2021), indicating that A . hydrophila infection brings damage to fish liver.…”
Section: Discussionmentioning
confidence: 99%
“…Cyprinus carpio can enhance the GOT and GPT activity in the serum (Krishnaveni et al, 2021), indicating that A. hydrophila infection brings damage to fish liver. While in this study, only GPT activity in the serum was significantly increased in LG and MG of WM-1+KS02 groups, and the enhancement of GPT activity was suppressed to the normal level in HG of WM-1+KS02 group.…”
Section: It Has Been Reported That a Hydrophila Infection In Common Carpmentioning
confidence: 99%